Pengaruh Faktor Internal Dan Eksternal Terhadap Minat Berwirausaha (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Prodi Manajemen Angkatan 2019) - Indah Ayu Lestari; Suwarto; Fitriani (Universitas Muhammadiyah Metro, 2025)
Due to the low level of student entrepreneurship, the author conducted research to see whatthe actual conditions are regarding interest in entrepreneurship among management studentsclass of 2019. The aim of the research is to determine the influence of internal and externalfactors on interest in entrepreneurship among management students class of 2019. The typeof research used in this research is quantitative research. Quantitative research methods area type of research whose specifications are systematic, planned and clearly structured fromthe start of creating the research design. The research results show that the influence ofinternal factors has a positive and significant effect on entrepreneurial interest. The influenceof external factors has a positive and significant effect on entrepreneurial interest. Theinfluence of internal factors and external factors together has a positive and significant effecton entrep